A combination of differentiation and consolidation theory and risk-benefit analysis to examine decisions on mastitis prevention. Issue 2 (1st February 2020) - Lind, Nina; Hansson, Helena; Emanuelson, Ulf; Lagerkvist, Carl Johan
Abstract: Mastitis infections cause severe pain in dairy cows and are the most costly illness to farmers. This study combined differentiation and consolidation (Diff-Con) theory with risk-benefit analysis to explore how risky decisions are perceived and justified after a decision has been taken. More specifically, using survey data from 428 Swedish dairy farmers, their decisions about adopting preventive measures to control mastitis (mastitis control options, MCO) in dairy herds were examined. The analyses included group comparisons with non-parametric rank tests and use of both ordinary least squared regression and seemingly unrelated regression analysis to examine how prior adoption of MCO affects farmers' attitudes to the MCO. The results showed that MCOs already adopted were rated higher in perceived riskiness (if not implemented) and in expected benefit (for illness prevention) than non-adopted MCOs. Having made the decision to implement a strategy increased the likelihood of that decision being perceived as more beneficial (reducing mastitis) and risky (in terms of disease increase if not implemented), irrespective of the combination of strategies used on the farm, during the post-consolidation stage. No difference in perceived illness prevalence could explain the farmers' rating of the MCOs. These findings suggest that there may be a path dependency in farmers' decision-making with respect to MCO. This implies that novel MCOs may have difficulty in achieving wider implementation. These results have implications for the development of strategies to communicate best practices for use of MCOs and for new research on MCOs and farmers' decision-making.